Leadership Perceptions, Educational Struggles and Barriers, and Effective Modalities for Teaching Vertigo and the HINTS Exam: A National Survey of Emergency Medicine Residency Program Directors - Mary McLean; Justin Stowens; Ryan Barnicle; Negar Mafi; Kaushal Shah (Western Journal of Emergency Medicine)
Introduction: The utility of the three-part bedside oculomotor exam HINTS (head impulse test, nystagmus, test of skew) in the hands of emergency physicians remains under debate despite being supported by the most recent literature. Educators historically lack consensus on how specifically to teach this skill to emergency medicine (EM) residents, and it is unknown whether and how EM residency programs have begun to implement HINTS training into their curricula. We aimed to characterize the state of HINTS education in EM residency and develop a needs assessment. Methods: In this cross-sectional study, we administered a survey to EM residency directors, the themes of which centered around HINTS education perceptions, practices, resources, and needs. We analyzed Likert scales with means and 95% confidence intervals for normally distributed data, and with medians and interquartile ranges for non-normally distributed data. Frequency distributions, means, and standard deviations were used in all other analyses. Results: Of 250 eligible participants, 201 (80.4%) responded and consented. Of the 192 respondents providing usable data, 149/191 (78.0%) believed the HINTS exam is valuable to teach; 124/192 (64.6%) reported HINTS educational offerings in conference; and 148/192 (77.1%) reported clinical bedside teaching by faculty. The most-effective educational modalities were clinical bedside teaching, online videos, and simulation. Subtopic teaching struggles with regard to HINTS were head impulse test and test-of-skew conduction and interpretation, selection of the correct patients, and overall HINTS interpretation. Teaching barriers centered around lack of faculty expertise, concern for poor HINTS reproducibility, and lack of resources. Leadership would dedicate a mean of 2.0 hours/year (SD 1.3 hours/year) to implementing a formal, standardized HINTS curriculum. Conclusion: Despite controversy surrounding the utility of the HINTS exam in EM, most residency directors believe it is important to teach. This needs assessment can guide development of formal educational and simulation curricula focusing on residency directors’ cited HINTS exam educational struggles, barriers, and reported most-effective teaching modalities.